2003
DOI: 10.1002/art.10950
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of clonal populations of dedifferentiated adult human articular chondrocytes

Abstract: Objective. To investigate whether adult human articular chondrocytes (AHACs), dedifferentiated by monolayer expansion, can differentiate toward diverse mesenchymal lineages and, if so, whether this ability is regulated by growth factors during monolayer expansion.Methods. AHACs were expanded as multiclonal or clonal populations in medium without (control) or with factors enhancing cell dedifferentiation (transforming growth factor ␤1, fibroblast growth factor 2, and platelet-derived growth factor type BB [TFP]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
319
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 344 publications
(343 citation statements)
references
References 42 publications
21
319
0
3
Order By: Relevance
“…22 Additional supplementation of TGF-b1 and PDGFbb to the culture medium during expansion did not further increase goat chondrocyte growth or GAG content in pellets, in contrast to recent findings with human chondrocytes. 13,29 These results indicate that mammalian chondrocytes share common paradigms of response to growth factors, but with species-related specificity, 30,31 thus highlighting the limit of using animal models for growth factor-based cartilage repair approaches.…”
Section: Discussionmentioning
confidence: 93%
“…22 Additional supplementation of TGF-b1 and PDGFbb to the culture medium during expansion did not further increase goat chondrocyte growth or GAG content in pellets, in contrast to recent findings with human chondrocytes. 13,29 These results indicate that mammalian chondrocytes share common paradigms of response to growth factors, but with species-related specificity, 30,31 thus highlighting the limit of using animal models for growth factor-based cartilage repair approaches.…”
Section: Discussionmentioning
confidence: 93%
“…However, in human diseases restricted to the articular cartilage, such as chondromalacia patellae, intense cell proliferation has been reported in the lesions as well as in the surrounding cartilage (35), which suggests that articular cartilage may contain resident cells that are sensitive to environmental cues and responsive to cartilage damage. Recently, Barbero et al reported that dedifferentiated adult human articular chondrocytes exhibited a differentiation plasticity (chondrocytic, osteoblastic, and adipocytic lineages), which was modulated by growth factors used during monolayer expansion and was highly heterogeneous across different clones (13).…”
Section: Discussionmentioning
confidence: 99%
“…Dedifferentiated chondrocytes are able to redifferentiate toward the chondrogenic lineage and to reexpress a chondrocytic phenotype when cultured in suspension, in agarose, with alginate beads, or on a hydrogel substrate in vitro (8,(11)(12)(13)(14)(15). Subcutaneous implantation of such dedifferentiated chondrocytes into the joints of nude mice can lead to redifferentiation, which is expressed by formation of cartilage nodules (16).…”
mentioning
confidence: 99%
“…In vitro differentiation was induced as previously described [19][20][21]. See Materials and Methods in Supporting Information.…”
Section: In Vitro Differentiationmentioning
confidence: 99%